Impact of Accumulated Dust on Performance of Two Types of Photovoltaic Cells: Evidence from the South of Jordan - Marashli, Abdullah; Al Shaba'an, Ghadeer Nyazi; Al-Twaissi, Waed; Shalby, Mohammad; Al-Rawashdeh, Hani (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
This paper examines the impact of accumulated dust on two types of photovoltaic (PV) cells in the performance of solar panels facility located in the southern part of Jordan between January to August 2020.Â To determine the performance of the solar PV panel system, two elements have been considered: sun radiation total efficiency and output power generated from the two types of the PV panel. Results of the study revealed that the mass of dust accumulated on the polycrystalline panel accumulated faster than on the cadmium telluride panel at a rate of 10.5 g/m2 for polycrystalline panels and 8.4g/m2 for cadmium telluride panel. Furthermore, results indicated that the projected drop in the efficiency of washed and unwashed polycrystalline panels decreased monthly by 5% and 16% respectively, while the efficiency of washed and unwashed cadmium telluride panels decreased monthly by 5% and 11.5% respectively. In the same context, results indicated that the wind speed, concentration rate, and relative humidity increased by 3%, 5%, and 8% respectively whereas the ambient temperature decreased by 4% monthly. On the other hand, the size and charge of accumulated dust on the cadmium telluride panel surface were larger than the size and charge of dust on the polycrystalline panel surface with a high percent of (Si) and low percent of (Ca) and (Fe). This research contributes to the literature by providing empirical evidence for the impact of accumulated dust on PV panels applied on a dusty-weather such as the one in the southern part of Jordan.